Proyecto de mejora de los procesos de selección, inducción y capacitación de personal en una empresa textil - Moreno Fajardo, Renzo Daniel (2022)
The present project titled as “IMPROVEMENT PROJECT OF THE PROCESSES OF SELECTION, INDUCTION AND TRAINING OF PERSONNEL IN A TEXTILE COMPANY » is based on the research about the processes of selection, induction and training of the company HIALPESA. To that end, an analysis of the processes was made, having as the main focus the macroprocess of Manufacture Operations, because of the big quantity of workers, the huge diversity of job positions and the high personnel turnover rate. Through this diagnosis, it was shown that the turnover rate is a constant problem on workers, generating production delays and cost overruns when this rate rises. As a result, the average departures per year was 1600, with an annual turnover rate upper 120%. It is possible to solve this problem from many ways, but the research detected that one of the main causes was the omission of the order or procedures of the processes of selection, induction and training. For this reason, the proposal of improvements of the processes of hiring was made, according to each job position, regarding the requirements and characteristics of each production area. It was demonstrated that the selection of personnel being made based on the job description with an ordered and methodic way, the coordination with the production managers and the continuity of the process over the year could reduce the personnel turnover rate by 26% and, above all, it could reduce by 47% the Laboral cost of the short-time hiring’s, because it represented a low productivity. These results have more than a year since the project was implemented, with the same procedures that are still improving.